Penyederhanaan Perizinan Lingkungan Hidup di Kabupaten/Kota Melalui Undang-Undang Nomor 6 Tahun 2023 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 Cipta Kerja Menjadi Undang-Undang - Erwin Prasetyo; Bayu Dwi Anggono; RA. Rini Anggraeni (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
The Job Creation Law contains various changes to the Environmental Protection and Management Law, one of which is the public's right to access environmental information. This can be seen in Article 22 of the Job Creation Law which amends Article 26 paragraph (2) of the Environmental Protection and Management Law, which stipulates that the public, especially environmental observers, must be involved in every activity carried out by business actors or activities, by providing open and complete information before the activity is carried out. The concept of Business Licensing in the environmental sector regulated in the Environmental Protection and Management Law using a permit-based approach has been changed to the application of standards and risk-based in Law Number 6 of 2023 concerning Job Creation, this means that the granting of permits will be carried out by the central government based on calculations of the level of danger and the potential value of danger to aspects of health, safety, the environment and/or utilization of resources. In addition, there is also the loss of participation of the affected community in all forms of decisions in the Environmental Impact Analysis (AMDAL) process which previously involved potentially affected communities, now only involving directly affected communities.